IMPLEMENTASI KOMUNIKASI TERAPEUTIK DALAM DAKWAH - Ari Wibowo (Jurnal Bimbingan Penyuluhan Islam, 2021)
Islamic therapeutic communication tries to give positive suggestions to patients by carrying out good communication interaction activities that in sickness and the problems of life there is a very big wisdom behind it. Therapeutic communication that is built will have a tremendous psychological impact on people who are sick or are experiencing very severe problems. Therefore, Islamic therapeutic communication is very important to restore the psychological state of someone who was originally down and then has the spirit again. Analysis and Steps of Therapeutic Communication in da'wah is essentially a form of interpersonal communication that is specifically aimed at the recovery process or certain therapy. Therapeutic communication in principle is professional communication that leads to goals, which are aimed at fostering a therapeutic relationship between nurses and clients, characterized by the exchange of behaviors, feelings, thoughts, and experiences in fostering therapeutic intimate relationships within a limited scope.